Sensitivity detection in memory recognition: interference control as index of taxonomic memory development?. Issue 2 (7th February 2020) - Artuso, Caterina; Palladino, Paola; Belacchi, Carmen
ABSTRACT: We investigated how long-term memory modulates recognition accuracy performance in typically developing primary school children (aged 7 vs. 9 years). We devised a verbal working memory task where words associations were manipulated to obtain different types of semantic associations (i.e., taxonomic, thematic). Sensitivity detection measures were operationalised as difference between hits and false alarms (for both internal and external intrusions). As our main result, we found sensitivity detection for taxonomic associations was greater in older children than younger. In turn, this showed that taxonomies produce more interference in younger children, and thus, they are not able to take advantage from taxonomic associations, as older children do. These results are helpful in sketching a developmental trend of how semantic memory impacts recognition processes in memory.